2005
DOI: 10.1039/b509102k
|View full text |Cite
|
Sign up to set email alerts
|

The unprecedented reaction of dimethylsulfonium methylide with Michael acceptors: synthesis of 1-substituted vinyl silanes and styrenes

Abstract: Rather than the usual cyclopropanation, conditions for an unprecedented elimination reaction from the adduct of dimethylsulfonium methylide and various Michael acceptors have been established leading to functionalized 1-substituted alkenes. In silyl substituted substrates (2a and 2h), where a facile Peterson-type olefination is possible from the adduct; elimination took place instead to give functionalized 1-substituted vinyl silanes. Aryl substituted Michael acceptors (2b-e, 2g and 2i-k) also underwent a simi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…We in our group were engaged in the synthesis of [3]­dendralenes for a couple of years, utilizing a sequential olefination methodology by employing dimethylsulfonium methylide. Initially, the dienylphosphonoacetates I were converted to dendralenes II by a Horner–Wadsworth–Emmons (HWE)-type olefination, but the terminally aryl-substituted [3]­dendralenes produced were so unstable that they underwent a rapid in situ cyclodimerization to provide highly functionalized cyclohexenes III with excellent regio- and stereocontrol (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…We in our group were engaged in the synthesis of [3]­dendralenes for a couple of years, utilizing a sequential olefination methodology by employing dimethylsulfonium methylide. Initially, the dienylphosphonoacetates I were converted to dendralenes II by a Horner–Wadsworth–Emmons (HWE)-type olefination, but the terminally aryl-substituted [3]­dendralenes produced were so unstable that they underwent a rapid in situ cyclodimerization to provide highly functionalized cyclohexenes III with excellent regio- and stereocontrol (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…n-BuLi (1.5 M in hexane), Me 3-S(O)I and Me 3 SI were purchased from Aldrich. Compounds 2a and 2d were prepared following our reported procedure [46]. The column chromatography was performed on silica gel (230-400 mesh).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we and others have shown that dimethylsulfonium methylide (DIMSY) (1) when used in excess, or in the presence of a base can act as an equivalent of a carbenoid to produce interesting product(s) when reacted with various Michael acceptors [45][46][47][48][49][50][51][52], activated dienes [53], carbonyl compounds, imines and epoxides [54][55][56][57]. For example, when DIMSY was reacted with b-silylmethylene or b-arylmethylene malonates 2, cyclopropane derivatives 3 or olefins 4 were obtained [45][46][47][48][49][50][51][52] depending upon the quantities of the ylide and base used (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…15 However, such types of reactions have not been applied to the synthesis of b-silyl-d-keto esters. We envisage an alternate and straightforward method that involves an atom-economic, 16 regio-and enantioselective, direct Michael addition of an alkyl methyl ketone to the bsilylacrylate 4 or (silylmethylene)malonate 5 17 (Figure 1). The Michael addition 18 is one of the most frequently used reactions because of its efficiency and effectiveness.…”
mentioning
confidence: 99%
“…Silylmethylene malonate 5 was prepared following a procedure reported by us. 17 Diphenylprolinol 6a was commercially available and its TMS ether 6b was prepared according to the literature 37 procedure. All the amino acids were purchased from commercial sources.…”
mentioning
confidence: 99%